Perancangan Basecamp Arsenal Indonesia Supporter di Surabaya - Ifan Setiawan; Andereas Pandu Setiawan; Poppy Firtatwentyna Nilasari (Intra, 2016)
Football is one of the sports that is loved by many people. Many fans of a club founded organizations in support of their beloved club. One of the clubs that have a lot of fans is Arsenal FC. In Indonesia, many fans have set up an organization called Arsenal Indonesia Supporter. Where they support Arsenal by watching alongside Arsenal's games and various other activities. But there's a lack of place to accommodate a wide range of activities of Arsenal Indonesia Supporter.